ESTUDOS TAXONÔMICOS DE UMA ESPÉCIE DE TRICHOMYCTERIDAE (SILURIFORMES) NA BACIA DO RIO IVINHEMA, ALTO RIO PARANÁ - DONI, Giovanna Lôbo,; DAGOSTA, Fernando César Paiva,; DONIN, Laura Modesti,; SÚAREZ, Yzel Rondon, (ANAIS DO ENIC, 2025)
-